KOMPARASI MIMO PADA SISTEM IRIGASI INDOOR DAN OUTDOOR DENGAN METODE FUZZY LOGIC - Rizky Pradana; Riri Irawati (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2018)
The process of plant irrigation can be done in an open or closed environment. Irrigation applied to the open environment such as for food production process and gardening. As for the closed environment, irrigation is usually done for the process of cultivating plants for example greenhouse. The problem raised in this research is a series of appropriate irrigation system for indoor and outdoor environment. The solution offered is the creation of two modules of automatic irrigation system that will be compared to get suitability to the application in indoor or outdoor environment. The method used is fuzzy logic with multiple input multiple output (MIMO) pattern which is assembled in a prototype model. The results obtained from this research is to determine the efficiency value between module 1 and module 2 with the result percentage of 78% better from the results of research module 2